(3eQTO GdeSJTGQ aj GOGQI GdehGO (B:s (3GdJNRjf hGdTQGA (B/s - (3eMeO ahRj, GdMGL Ndjds ((3YeGf(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 1990)
(3aUd JegjOj (B1-(3eYdheGJ CSGSjI (B2- (3GdTQGA (B3- (3GdJNRjf (B4- (3GdehGO GdaGFVI hZjQ GdUGdMI (B5- (3Gdfbd hGdJhRjY (B6- (3GdYgO hGdLQO (B7- (3eMGSHI GdeNGRf (B8- (3Gdeaghe GdMOjK dGOGQI GdMhGQ (B9- (3OQGSI eSJfOGJ hfeGPL GdTQGA hGdJNRjf (B10-(3JOQjH hJCgjd GdehXajf (B11-(3GdQbGHI GdNGQLjI edGMb HGdOdjd GdCeQjcj ddeLehYGJ hGdaUhd(B.(3, eQGLY eNJGQIs
Keywords: (3GOGQI GdehGOs; (3GdJNRjfs; (3TQGAs